A survey of factors contributing to language change in English, with special reference to lexical change - Mohideen, Haja; Mohideen, Shamimah (2008)
The purpose of this paper is to create awareness among language users of the need to be current with our knowledge of lexis. Older and contemporary dictionaries as well as popular reading materials were used to investigate lexical change.It was found that certain lexical items had acquired additional meaning. Some were gradually being replaced by others. There was variation between varieties of English. Some were becoming old-fashioned in the modern context. Words which were considered formal are also being used casually. Certain vocabulary items were unpredictable in meaning. It was also found that there were many euphemistic, non-sexist and new coinages.